Harnessing associational networking and social capital for development in West Africa (2016)
Within the past three decades, widespread poverty has accompanied Western influenced neoliberal policies often camouflaged as vital development initiatives (e.g. SAP and privatization programme). Still, within the same period, the continent has witnessed spontaneous emergence of numerous associational groups; created through social networking for the utilization of social capital for the satisfaction of individual and group development needs as strategy against poverty. These associations are usually in form of cooperative, welfare, town and/or friendship groups. It is important to note that a basic feature of the associations, especially, in terms of social networking for social survival is related to the communal value of African societies as against the modernist/Western preference for individuality. The aim of the article is to examine the relevance of associational groups to the development of West Africa with the primary objective of presenting a possible policy position on harnessing associational networking and social capital for development in West Africa.